Postoperative haemodynamics in tetralogy of Fallot. A study of 132 children. - Joransen, J A (1979)
Our study was undertaken to determine the type, incidence, and functional significance of residual anomalies in patients who have undergone corrective repair for tetralogy of Fallot. We reviewed data from cardiac catheterisations performed on 132 survivors. A significant residual ventricular septal defect was present in only 12 patients. Resting right ventricular systolic pressure was less than 80 mmHg in 100 patients and ranged from 80 to 150 mmHg in the other 32 patients. Thirty-five patients were studied both at rest and during supine exercise. In most patients, the relation between oxygen consumption and cardiac output was normal during exercise. The stroke index and right ventricular end-diastolic pressure at rest and on exercise were compared in 34 patients. Seventeen showed a normal response to exercise. In the other 17 patients, right ventricular end-diastolic pressure rose on exercise; in 5 of these the stroke index fell during exercise, indicating abnormal myocardial response. Our studies indicate the frequent occurrence of residual abnormalities, even in patients who appear asymptomatic, after total correction of tetralogy of Fallot.